CYCLICAL ANALYSIS OF TRADE DYNAMICS IN NIGERIA - Apere, ThankGod Oyinpreye (Advances in Social Sciences Research Journal, 2015)
ABSTRACT This study using first differenced VAR(1) model attempted a cyclical analysis of trade dynamics in Nigeria over the period 1981 – 2012. Two historical business cycle troughs in 1985 and 2001 were identified. Results showed no evidence supporting the assertion that non-oil trade has contributed to economic recoveries in Nigeria. Furthermore nominal shocks dominated output shocks in explaining changes in trade variables. It was therefore recommended that, to better tap from the global resource base the monetary authority in Nigeria should apply sound monetary policy during periods of recession to stimulate output growth and quick recovery. Key Words: Cyclical Analysis, Trade Dynamics, VAR, Shocks, Non-oil trade.